Influencer Marketing dan Content Marketing Sebagai Antecedent Purchase Intention Produk The Originote : Studi Pada Konsumen Marketplace - Dita Viviana; Kristina Anindita Hayuningtias (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research will examine how influencer marketing and content marketing as antecedents of purchase intention for The Originote products using quantitative data where the results of this research will be in the form of numbers processed using IBM SPSS 22 software. The population used is consumers who know The Originote products and have the intention of buying The Originote products in the Marketplace. The sampling technique applies the non-probability sampling method through a purposive sampling approach, namely the selection of respondents based on certain criteria or characteristics that have been previously determined. Data collection using a questionnaire with a five-level Likert measurement scale (1 to 5). From this process, data was obtained as many as 170 respondents. Furthermore, the data collected was tested with the linear regression method. The findings show that influencer marketing has a positive and significant influence on purchase intention. Furthermore, content marketing has a positive and significant influence on purchase intention. This shows that the more famous and the more followers the influencer has, the more consumers will believe in what he is promoting. Meanwhile, the more relevant, informative and interesting the content created, the more it will foster consumer intention to buy.